FAKTOR-FAKTOR YANG MEMPENGARUHI AGLOMERASI DI KABUPATEN BANDUNG BARAT - Budi Santosa; Shafira Putri Salsabila; Soeharjoto Soeharjoto (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
The aim of this study is to analysis factors that affect the Agglomeration at West Bandung Regency in 14 districts. This study uses panel regression analysis with the help of Eviews analysis 9. The data used in this research is the growth of the GDP data, the human development index and the number of inhabitants of the 14 Subdistricts in 2014 to 2016 period (42 observations). The results show that economic growth has no effect the agglomeration, while the human development index and population has a positive effect on agglomeration. From the results obatained, there are 3 sub districts that have perfectly impact of Agglomeration. The sub districts are Lembang, Ngamprang and Padalarang.